Food for thought: pretty good multispecies yield. (12th May 2016) - Rindorf, Anna; Dichmont, Catherine Mary; Levin, Phillip S.; Mace, Pamela; Pascoe, Sean; Prellezo, Raul; Punt, André E.; Reid, David G.; Stephenson, Robert; Ulrich, Clara; Vinther, Morten; Clausen, Lotte Worsøe
Abstract: MSY principles for marine fisheries management reflect a focus on obtaining continued high catches to provide food and livelihoods for humanity, while not compromising ecosystems. However, maintaining healthy stocks to provide the maximum sustainable yield on a single-species basis does not ensure that broader ecosystem, economic, and social objectives are addressed. We investigate how the principles of a "pretty good yield" range of fishing mortalities assumed to provide >95% of the average yield for a single stock can be expanded to a pretty good multispecies yield (PGMY) space and further to pretty good multidimensional yield to accommodate situations where the yield from a stock affects the ecosystem, economic and social benefits, or sustainability. We demonstrate in a European example that PGMY is a practical concept. As PGMY provides a safe operating space for management that adheres to the principles of MSY, it allows the consideration of other aspects to be included in operational management advice in both data-rich and data-limited situations. PGMY furthermore provides a way to integrate advice across stocks, avoiding clearly infeasible management combinations, and thereby hopefully increasing confidence in scientific advice.